P2.081 Antimicrobial Susceptibilities of Neisseria Gonorrhoeae Strains from Male Urethritis in Japan -the First National Surveillance. (13th July 2013) - Hamasuna, R; Yasuda, M; Ishikawa, K; Uehara, S; Takahashi, S; Hayami, H; Yamamoto, S; Matsumoto, T; Hanaki, H; Kadota, J
Abstract : Background: Neisseria gonorrhoeae is one of the most important pathogens causing sexually transmitted infection. Resistant N. gonorrhoeae trains against several antimicrobials are increasing worldwide. Purpose: In this study, the trends of antimicrobial susceptibilities among N. gonorrhoeae strains isolated from male patients with urethritis were investigated as the first Japanese national surveillance, which was conducted by the surveillance committee of three Japanese societies as Japanese Society of Chemotherapy, Japanese Association of Infectious Diseases and Japanese Society of Clinical Microbiology. Methods: The targets were male patients older than 16 years with urethral discharge and symptoms of urethritis. The patients were diagnosed with gonococcal urethritis by a clinician at 51 participating facilities. The period of specimen collection was between April 2009 and October 2010. Results: Of the 156 specimens, 83 N. gonorrhoeae strains were tested for antimicrobial susceptibilities to 18 agents. The prevalence of β-lactamase producing strains and chromosomally-mediated resistant strains were 7.2% and 16.5%, respectively. Against cepharosporins, one strain was resistant to cefixime with MIC 0.5 μg/ml. There was not resistant strain to ceftriaxone, but the 7 strains (8.4%) had MIC 0.125 μg/ml. The MIC of fluoroquinolones to all strains showed a bimodal distribution. The values of MIC90 of ciprofloxacin and levofloxacin were 16 and 8 μg/ml, respectively. Sitafloxacin, one of fluoroquinolones had strong activity to N. gonorrhoeae strains and the value of MIC90 was 0.25 μg/ml. The MIC of azithromycin in 2 strains was 2 μg/ml, but no high-level resistance to macrolides was detected. Conclusion: The first national surveillance for antimicrobial susceptibilities of N. gonorrhoeae was performed. Fluoroquinolone-resistance N. gonorrhoeae strains were spread in Japan. The resistant rate of azithromycin resistant was 2.4%.